2017
DOI: 10.1002/ece3.2707
|View full text |Cite
|
Sign up to set email alerts
|

VIM‐1 carbapenemase‐producing Escherichia coli in gulls from southern France

Abstract: Acquired carbapenemases currently pose one of the most worrying public health threats related to antimicrobial resistance. A NDM‐1‐producing Salmonella Corvallis was reported in 2013 in a wild raptor. Further research was needed to understand the role of wild birds in the transmission of bacteria resistant to carbapenems. Our aim was to investigate the presence of carbapenem‐resistant Escherichia coli in gulls from southern France. In 2012, we collected 158 cloacal swabs samples from two gull species: yellow‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 39 publications
(55 reference statements)
4
37
0
1
Order By: Relevance
“…Different eating habits affect the occurrence of E. coli found in wild birds, as reported by some studies (Sharma et al, 2018;Vittecoq et al, 2017). From this current study, it was found that the birds displayed higher occurrence of E. coli.…”
Section: Occurrence Of C Jejunisupporting
confidence: 75%
“…Different eating habits affect the occurrence of E. coli found in wild birds, as reported by some studies (Sharma et al, 2018;Vittecoq et al, 2017). From this current study, it was found that the birds displayed higher occurrence of E. coli.…”
Section: Occurrence Of C Jejunisupporting
confidence: 75%
“…Wildlife acquires CRE for example by contact with sewage, manure, or waste disposal sites [93]. Importantly, we found several reports describing CRE in swallows, black kites, storks, or gulls (with a high prevalence in France and Australia), demonstrating that these birds may act as reservoirs for bla NDM , bla OXA-48 , bla IMP , bla VIM-1 , and bla KPC-2 [25,78,79,82,83,85]. These findings raise concern because they indicate that these carbapenemases are prevalent in the environment in amounts that not only lead to colonization of wildlife, but also because these (migratory) birds may act as vectors facilitating the spread of CRE beyond borders of farms, dwelling zones, countries, or even continents.…”
Section: Discussionmentioning
confidence: 60%
“…specimen tested) [77,79,82]. In companion animals, 2.4e4% of cats, 1.5e2.6% of dogs, and 4% of horses tested in Algeria [67,68], as well as 0.6% of the dogs in France and Spain carried CRE [70,73].…”
Section: Prevalence Of Crementioning
confidence: 96%
See 1 more Smart Citation
“…Among wildlife, two studies found a high prevalence of CRE among silver gulls and yellow-legged gulls in France (19.4%) [4]. The occurrence of CRE in livestock, seafood, wildlife, pets, and directly exposed humans poses a risk for public health.…”
Section: Introductionmentioning
confidence: 99%